High-frequency Digital Lock-in Amplifier Using Random Sampling - Sonnaillon, Maximiliano Osvaldo (2008)
A high-frequency digital lock-in amplifier (LIA) that uses a random-sampling scheme is proposed and tested experimentally in this paper. By using this sampling strategy, it is possible to process, without aliasing effects, periodic signals of frequencies that are several times higher than the Nyquist frequency. Analytical and numerical analyses that show the advantages and limitations of the proposed scheme are presented. A high-frequency digital LIA implementation is also described. The prototype maximum sampling frequency is 150 kHz, and its maximum signal frequency without aliasing is 2.5 MHz, limited only by the random-sampling period quantization. Experimental results that validate the proposal are presented.